2010
DOI: 10.1590/s0100-69912010000400011
|View full text |Cite
|
Sign up to set email alerts
|

Ação da laserterapia no processo de proliferação e diferenciação celular: revisão da literatura

Abstract: O uso da luz laser de baixa intensidade vem sendo utilizado como terapia coadjuvante ou de forma terapêutica isolada em várias especialidades odontológicas. Suas principais indicações incluem ação anti-inflamatória, analgésica e indutora da reparação tecidual. O poder cicatrizante do laser de baixa potência é discutido neste trabalho assim como os mecanismos de biomodulação e estimulação da mitose. Estas propriedades, já estudadas em células benignas, quando aplicadas em células neoplásicas malignas, abrem esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
24

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 29 publications
1
21
0
24
Order By: Relevance
“…Using higher doses would have a greater destructive effect. 9,19,20 Nussbaum et al reaffirmed this finding by investigating the in vitro bacterial growth of Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli when irradiated with laser of 630 m h, h 660 m, 810 I 905 hh m (doses ranging from 1J/cm 2 and 50J / cm 2 ). The results showed the existence of different values of wavelength and doses for inhibiting each type of bacteria 4.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Using higher doses would have a greater destructive effect. 9,19,20 Nussbaum et al reaffirmed this finding by investigating the in vitro bacterial growth of Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli when irradiated with laser of 630 m h, h 660 m, 810 I 905 hh m (doses ranging from 1J/cm 2 and 50J / cm 2 ). The results showed the existence of different values of wavelength and doses for inhibiting each type of bacteria 4.…”
Section: Discussionmentioning
confidence: 91%
“…Lower doses cause stimulation of cellular activity and high doses inhibit cellular growth. 9 ,10 A number of studies have been conducted on the effect of laser on infected wounds. Santos et al for example observed, using histological analysis, the healing of wounds infected with S. aureus when treated with laser at a dose of 5J/cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…T he incorporation of laser as a therapeutic tool has been accompanied in the biomedical field since 1960 by Theodore Maiman. One of the first published experiments on the effects of low-level laser dates from 1983, with HeNe (Helium Neon) laser irradiation of wounds in rats for 14 consecutive days 1 .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…The possibilities of laser use have increased, and its use has been widespread in all different areas of medicine and dentistry, presenting itself as an excellent option for health care. [2][3][4] The development of different types of lasers enabled the study for their use in various therapeutic and surgical procedures. Low level lasers have been developed for therapeutic use.…”
Section: Introductionmentioning
confidence: 99%